ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DALAM MEMINIMASI BIAYA PRODUKSI DI PT VOLEX BATAM - Marpaung, Richad; Susanti, Elva (Computer Science and Industrial Engineering, 2022)
Policy in determining the level of control of raw material inventory that must be maintained, by placing orders to increase inventory to be made and how large orders must be held. Cable raw material inventory data for several months, such as in March 2021 the company experienced an excess of 3,000 pcs of raw materials, in April 2021 there was a shortage of raw materials of 500 pcs, and the biggest shortage occurred in December 2021, which was 4,000 pcs. occurs due to erratic demand from customers so that companies often experience shortages and excess raw materials, sometimes shortages of raw materials for delivery occur from suppliers who arrive late. The method used in this research is the method of Economic Order Quantity (EOQ) and Silver Meal. The results of calculations using the Economic Order Quantity (EOQ) inventory model, obtained the number of orders for one order of cable raw materials is 39,200 pcs. Then for the safety stock of cable raw materials outside the routine needs of cable raw materials as many as 23 pcs. The results of the calculation of the time for reordering raw materials are 1,640 pcs. The total cost that must be incurred by the company if using the Economic Order Quantity (EOQ) inventory model is Rp. 11,091,666, - and using the Silver Meal method the company incurs a cost of Rp. 8,241,666, - for cable raw materials.